Effect of The Use of Different Whey Proteins on Some Properties of Sahlep Beverage Prepared from Functional Sahlep Powder - Kurban Yaşar; Adnan Bozdogan (Turkish Journal of Agriculture: Food Science and Technology)
Sahlep powder is obtained by drying and grinding after the plant tubers of the Orchidaceae family removed from the soil. Sahlep powder, which is unique to Turkey, is used in Maras ice cream, sahlep beverage and medicine production. There is a growing interest in healthy nutrition in the world. This increasing is increased the demand for functional food. Whey proteins are increasingly used in foods in recent years due to the functional compounds they contain. In this study, it was tried to increase the functional properties of sahlep using Whey proteins. For this purpose, different Sahlep powder was prepared by using Whey protein concentrate (WPC 35%), demineralized whey protein powder, milk powder, sahlep, sugar, starch, cinnamon and ginger. The different Sahlep produced were made into sahlep beverage with water and pH, viscosity and sensory analysis were made. As a result of the analyzes made, the use of Whey proteins statistically affected the viscosity value of the sahlep beverage. It was determined that the use of different whey proteins affected the color, taste and smell values of Sahlep. As a result of the sensory evaluation performed by the panelists, sahlep beverage produced in 25% whey protein concentrate (WPC 35%) + 75% milk powder mixture was preferred. It is may be suggested to produce sahlep powder and sahlep beverage by using 25% whey protein concentrate (WPC 35%) + 75% milk powder mixture.